Sustainable Energy and Mobility as Drivers for the Economic Growth in the Mediterranean Islands - Theocharis Tsoutsos (Renewable Energy and Sustainable Development, 2018)
The “greening” of the inhabitant Mediterranean islands is crucial in order to build a sustainable future. Furthermore, the islands consist a major global tourism destination, so the potential minimization of their carbon footprint is essential for the success of the Paris Agreement. The islands have the potential to be frontrunners in the clean energy transition by adopting new technologies, implementing and demonstrating innovative solutions, also for transport.  However, there is a number of challenges for their smooth operation and sustainability, such as: Energy safety, space use, road safety, air quality and noise pollution are some transport related issues that islands have to cope with. Islands are attractive as touristic destinations, feature a high pressure to their fantastic nature and sensitive ecosystems, which need special care and protection The seasonal fluctuation in their operation impacts on the design of their necessary infrastructure (ports, roads, energy supply systems) Although they should comply with the most recent national and international commitments, they are missing capacity, resources and social preparation for these changes. Fostering a Mediterranean insular sustainable energy and mobility approach will also support the development of innovative, quality tourism products and services to make destinations even more attractive, as well as to address the mobility needs of citizens and visitors. The above approach was discussed during the Public Hearing organized by the Network of the Insular Chambers of Commerce and Industry of the European Union (INSULEUR) and the Renewable and Sustainable Energy Systems Lab of the Technical University of Crete (ReSEL-TUC) on Friday 8th of June 2018 at the premises of the European Economic and Social Committee (EESC), in Brussels. The event was organised in partnership with the EESC and was supported by the Conference of Peripheral Maritime Regions (CPMR) and the European Small Islands Federation (ESIN).